ORGANIZATIONAL MECHANISM FOR THE DEVELOPMENT OF STATE PROGRAMS FOR POVERTY REDUCTION - MIRZAKHALIKOV, BOBIR (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
In the conditions of market relations, the financial policy of the state plays a decisive role in achieving the specific goals of ensuring the socio-economic development of the country. Financial policy creates conditions for the fulfillment of the most pressing tasks in society. Fiscal policy, on the one hand, is financial formation and direction of resources, and on the other hand, serves as a tool to influence economic interests. By conducting an effective macroeconomic policy, ensuring stable economic growth, and improving the business environment in the country a system of implementation of an acceptable state policy on poverty reduction has been developed and is being successfully implemented. But there are some theoretical, methodological and practical problems of the issue, which require the development of relevant conclusions and scientific recommendations after researching it.